ASPEK HUKUM PENJUALAN MINERAL IKUTAN BERUPA PASIR KUARSA OLEH PERUSAHAAN PEMEGANG IUP OP TAMBANG KAULINE - Sudaryat (Jurnal Hukum dan Bisnis (Selisik), 2022)
Mineral mining activities, both metallic and non-metallic minerals, generally produce main minerals and associated minerals. The amount of the main mineral with associated minerals varies depending on the mineral itself. For nonmetallic minerals in the form of kauline as the main mineral and quartz sand as an accompanying mineral, the percentage is 30 percent compared to 70 percent. The amount of associated minerals of quartz sand is more than that of kauline as the main mineral. Due to this fact, miscommunication often occurs which leads to disputes regarding the rights of mining companies to certain types of non-metallic minerals, namely kauline with a mineral as a by-product in the form of quartz sand, between mining companies and communities around the mine represented by local NGOs and their solutions. The results of the study were analyzed using a qualitative juridical method. The results showed that the holder of the IUP OP of the Kauline Commodity has the right to sell quartz sand as a byproduct after conducting a feasibility study and paying a production fee as stated in Article 59 of the Minister of Energy and Mineral Resources Regulation No. 7 of 2020. If there is a difference of opinion regarding the sale of quartz sand as a co-mineral between the NGOs around the mine representing the voices of the community around the mine and the company holding the IUP OP, efforts should be made to resolve the dispute outside the court in the form of consultations with the Ministry of Energy and Mineral Resources, negotiations between the companies holding the IUP OP and NGOs and if not achieved, proceed with mediation involving the local government as a mediato